(untitled) (Perner’s Contacts, 2008)
Servicing a large number of customers in a city zone is often a part of many logistics chains. This problem is often called a Street Routing Problem (SRP). The main problem of SRP is that, when the number of customers is large, the number of delivery path combinations becomes enormous. As presented in the paper, only using decision support systems such as Geographical Information Systems (GIS) is it possible to effectively manage SRP. Several new and known heuristics for solving SRP are evaluated on the real data and then compared. One of the key properties of GIS for use with the routing software is its flexible interactive and user-friendly environment. Routing software can find a good solution and explore the possibilities while an expert can then change the calculated routes to explore other possibilities based on the expert’s judgment. Other Decision Support Systems that solve SRP are presented as TRANSCAD developed by Caliper Corporation or GeoRoute developed by Canadian Post and GIRO.